Profile and Role of Serum Hypothalamic-Pituitary-Testicular-Axis Hormones on Sexual Function of Older Men with Type-2 Diabetes - Babatunde Ishola Gabriel Adejumo; Grace Umahi-ottah; fidelis oyakhire; Olufunke Victoria Aiyegbusi; Uchechukwu Dimkpa; Oladimeji Nasiru Abdulrahman; Emmanuel Ojeideleko Akhaumere; Simon Uzor (Medical Laboratory Technology Journal, 2023)
Little information is available on the complex endocrinology of sexual dysfunction, which is frequently associated with ageing and diabetes. We wanted to examine the serum profile of hypothalamic-pituitary-testicular-axis (HPTA) hormones and how they relate to sexual function in older men with type-2 diabetes. This study included 74 participants (44 type-2 diabetics and 30 healthy controls). The enzyme-linked immunosorbent assay (ELISA) method was used to measure serum levels of total testosterone (Te), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL). Compared to controls, diabetic patients had significantly higher FSH and PRL levels but lower Te levels. Testosterone was found to be significantly correlated with sexual intercourse frequency (p<0.01), erectile function, and libido (p< 0.001). We discovered significant (p < 0.001) relationships between libido, penile erection, and FSH, as well as between PRL and libido (p< 0.05). When compared to the other hormones, testosterone had the strongest associations with the frequency of sexual intercourse (p< 0.05), libido (p< 0.05), and penile erection (p< 0.01). Our findings indicated that HPTA hormones might have a significant influence on sexual functions in type-2 diabetic patients, with Te being the most important HPTA hormone influencing sexual functions in diabetic patients. This study, therefore, helps to clarify the complex endocrinology and physiology of the sexual dysfunction frequently observed in older men with type-2 diabetes and also supports the use of testosterone replacement therapy in older diabetic adults.